Iniciativas para planejamento de campanhas oculares: revisão da literatura - Silva Filho, Jose Verissimo Da [UNIFESP] (2019)
Introduction: Actions related to the causes of blindness and ways of avoiding them, such as disseminating information, promoting the dissemination of campaigns in the mass media, joint efforts, and health services are fundamental. The principle that is made to give meaning to the question: "What is it?" Researches the theme "Priority in planning in health management: educational impact and prevention in ophthalmology". Objective: To identify initiatives in the planning of ocular disease campaigns, through analysis of scientific articles, aimed at the education and prevention of ophthalmological diseases related to the causes of blindness, and how to avoid them. Method: The present study is an integrative review of the literature that aimed to search for scientific articles in relation to planning in the management of health and education of the population, in relation to ophthalmological diseases and their prevention. For data collection, the Scientific Electronic Library Online (SciELO) was used. Initially, 120 articles were found in the period from 2012 to 2018. Of these, only 10 presented aspects related to the theme and were in agreement with the objectives. Results: The results indicate that it is necessary to make the population aware of the importance of ophthalmologic treatment to the care and prevention of eye health, avoiding blindness so that the population lives with a better quality of life. Based on the analysis of the main ophthalmologic diseases and preventive actions in ocular health, there is a need for greater dissemination of ocular health prevention in different media. Conclusion: From this study, it is identified that the joint effort is fundamental so that it can diagnose and correct ophthalmological problems, analyze the difficulties of access to the ophthalmologist and correct the lack of information. It is important that planning to pass the population in general, mean of prevention of ophthalmological health, promoting joint efforts, informing places, facilitating access to patients, and qualifying professionals.